Multi-criteria decision making process based on some single-valued neutrosophic Dombi power aggregation operators - Jana, Chiranjibe; Pal, Madhumangal (Soft computing (Berlin, Germany), 2021)
The single-valued neutrosophic sets (SVNs) have a lot of applications in the field of engineering and scientific problems. In this paper, the Dombi operations and power averaging operator is used to constructing some single-valued neutrosophic Dombi power operators, i.e., single-valued neutrosophic Dombi power weighted averaging (SVNDPWA) operator, single-valued neutrosophic Dombi power order weighted averaging operator and single-valued neutrosophic Dombi power hybrid weighted averaging operator, and single-valued neutrosophic Dombi power weighted geometric averaging (SVNDPWGA) operator, single-valued neutrosophic Dombi power order weighted geometric averaging operator, and single-valued neutrosophic Dombi power hybrid weighted geometric averaging operator have been proposed. Some useful properties of these operators are investigated. Furthermore, SVNDPWA and SVNDPWGA operators in SVN environment are utilized to develop a multiple-criteria decision making (MCDM) method. Finally, an application of the proposed MCDM method is given for road construction companies selection. Also, for selection of road construction companies by single-valued neutrosophic Dombi power aggregation operators is verified by MABAC method. The proposed method is compared with some pre-existing techniques to check the efficiency of the proposed approach.